(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
The intermolecular interactions and solvation processes in solutions of acrylonitrile (AN) with dymetylsulfoxide (DMSO) using spectral (IR, UV, DRS) and physicochemical (viscometry, electrocunductimetry) methods have been investigated. It was shown that under the action of AN occurs destruction of assosiations of molecules DMSO, which is accompanied by partial ionizing the molecules AN and formation of new assosiations between molecules DMSO and AN. There is installed that in dymetylsulfoxide solutions AN up to 0.6 mole fraction of DMSO dominate assosiations AN. With the increase of concentrations of sulfoxide (from 0.6 up to 0.8 mole fraction) new assosiations between DMSO and AN with composition 2DMSO : AN are formed. In more concentrating sulfoxide solutions (XDMSO>0.8) dominate round-robin dimers of DMSO. Intermolecular interactions between AN–AN, AN–DMSO and DMSO–DMSO, mainly, have dipole-dipolar nature.